New species and new records of millipedes of the genus Rhinocricus Karsch, 1881 (Spirobolida: Rhinocricidae) from southern Brazil - Rodrigues, Patrícia E.s.; Ott, Ricardo; Rodrigues, Everton N.l. (Zootaxa, 2012)
Until now no species of Rhinocricus have been described or registered for the state of Rio Grande do Sul, Brazil. In thiswork we describe and illustrate five new species of Rhinocricus from Rio Grande do Sul: R. itauba sp. nov., R. gauchussp. nov., R. guaritas sp. nov., and R. serranus sp. nov., described from specimens of both sexes, and R. vacariensis sp. nov.based on a single male. The species R. divaricatus, R. padbergi and R. serratus are registered for the first time for this state. A key to Rio Grande do Sul species is presented.